Antibiotic Use Metrics to Guide Antibiotic Stewardship Priorities: Dental Antibiotic Prescribing in the U.S. Veterans Affairs (VA) System. (4th October 2017) - Suda, Kj; Fitzpatrick, Margaret; Gibson, Gretchen; Jurasic, Marianne; Miskevics, Scott; McGregor, Jessina C; Ramanathan, Swetha; Evans, Charlesnika
Abstract: Background: In the private sector, dentists prescribe approximately 1 out of every 10 antibiotic prescriptions and are the top specialty prescriber of antibiotics. However, antibiotic prescribing practices of VA dentists have not been reported. Standardized metrics of antibiotic consumption (ie, antibiotic days) are useful to guide stewardship efforts, but have not been reported for dentistry. Thus, the purpose of this study was to report antibiotic use metrics in the VA with an emphasis on antibiotics prescribed by dentists. Methods: Cross-sectional study of all Veteran users of VA dental care from all dental clinics ( n = 205) in 2013. Antibiotic data were collected at the patient-level where >1 day and/or >1 dose of a systemic antibiotic was ordered and dispensed. Metrics included: antibiotic days (AD; average number of days/patient where any antibiotic was administered) and days of therapy (DOT; average number of days/patient where a unique agent was administered). Dentists were identified by VA personnel files with the professional designation of 'Dentistry.' Antibiotics in the carbapenem, quinolone, anti-pseudomonal penicillin, third-/fourth-generation cephalosporin, macrolide, tetracycline, and aminoglycoside classes were considered to be broad spectrum. Student's t -test was used for statistical analysis; P < 0.05 was considered significant. Results: In 2013, >1 antibiotic dose/day was prescribed to 16.2% of VA dental patients (total = 476, 451 patients). By class, aminopenicillins were most frequently prescribed (69.4%), followed by lincomycins (21.9%). The overall mean AD was 11.4 (range = 1–309) days and DOT was 11.5 (1–309). Of the Veterans who received an antibiotic from a dentist, only 2.3% received a broad-spectrum agent. However, broad-spectrum AD (15.0) was significantly longer than narrow spectrum AD (11.2; P < 0.0001). Conclusion: While the prevalence of broad-spectrum prescribing was low, the patient-level duration of antibiotics prescribed by VA dentists is surprising. Thus, there may be an opportunity to expand antimicrobial stewardship efforts to dental providers. Disclosures: J. C. McGregor, Merck & Co.: Grant Investigator, Research grant